A systematic review of randomized controlled trials of interventions designed to decrease child abuse in high-risk families. (March 2017) - Levey, Elizabeth J.; Gelaye, Bizu; Bain, Paul; Rondon, Marta B.; Borba, Christina P.C.; Henderson, David C.; Williams, Michelle A.
Abstract: Child abuse is a global problem, and parents with histories of childhood abuse are at increased risk of abusing their offspring. The objective of this systematic review is to provide a clear overview of the existing literature of randomized controlled trials evaluating the effectiveness of interventions to prevent child abuse. PubMed, PsychINFO, Web of Science, Sociological Abstracts, and CINAHL were systematically searched and expanded by hand search. This review includes all randomized controlled trials (RCTs) of interventions designed to prevent abuse among mothers identified as high-risk. Of the eight studies identified, only three found statistically significant reductions in abuse by any measure, and only two found reductions in incidents reported to child protective services. While much has been written about child abuse in high-risk families, few RCTs have been performed. Only home visitation has a significant evidence base for reducing child abuse, and the findings vary considerably. Also, data from low- and middle-income countries are limited.